The Effects of Using the Picture Word Inductive Model on Word Pronunciation Reading Ability and Thai Communicative Writing of Grade 1 Students at Bannanakhae School in Surat Thani Province - Sriyapai, Jaruwan; Yahakorn, Suwannee; Anaman, Apirak (MCU Haripunchai Review, 2026)
The objectives of this research were: (1) to compare the reading aloud ability of Grade 1 students after being taught through the Picture Word Inductive Model (PWIM) with the 70 percent criterion, and (2) to compare the Thai written communication ability of Grade 1 students after being taught through the Picture Word Inductive Model with the 70 percent criterion This study employed a one-group posttest-only design. The population consisted of five Grade 1 students from Ban Nakhae School, under the Office of Surat Thani Primary Educational Service Area 2, during the first semester of the 2025 academic year. The research instruments included: (1) lesson plans based on the Picture Word Inductive Model, (2) a Thai word reading aloud ability test, and (3) a Thai written communication ability test. The statistics used for data analysis were percentage, mean, and standard deviation. The research findings were as follows: 1)The comparison of students’ reading aloud ability after the learning management using the Picture Word Inductive Model with the 70 percent criterion revealed that the mean score was 17.20, with a standard deviation of 1.64 and an average percentage score of 86, which was higher than the 70 percent criterion. 2)The comparison of students’ Thai written communication ability after the learning management using the Picture Word Inductive Model with the 70 percent criterion showed that the mean score was 17.80, with a standard deviation of 1.30 and an average percentage score of 89, which was higher than the 70 percent criterion.